EDITORIAL - Hayes, Grahame (PINS-Psychology in Society, 2025)
PINS (Psychology in society) does not often write editorials these days, and only does so when there is a special issue and the guest editors want to introduce the special edition, or when the editors want to communicate something to the subscribers and readers. For this issue, the first thing we want to communicate is an apology for the lateness of the issue, still dated 2011! PINS is committed to producing at least two issues per year, and hence the need to date this late issue, PINS 42, 2011. We shall attempt to be more timely in future. The main reason for our somewhat irregular production schedule has to do with our independence, which has the effect of leaving us with no infrastructural support to ensure a highly efficient and regular production timetable. We are working on solving this problem and thus ensuring a more regular operation.